Neural adaptation reveals state-dependent effects of transcranial magnetic stimulation. - Silvanto, J; Muggleton, N; Cowey, A; Walsh, V (2007)
Transcranial magnetic stimulation (TMS) is now widely used as a 'virtual' lesion paradigm to investigate behavioural functions, but the mechanisms through which it influences neural processing are unclear. To understand the differential effects of TMS on spatially overlapping populations of neurons we manipulated the relative activity levels of visual neurons by adapting subjects to a range of visual stimuli. By applying TMS to the visual cortex representing the central visual field we have shown in two experiments that the behavioural and perceptual effects of TMS depend on the state of adaptation of the neural population stimulated by TMS. Specifically, we have demonstrated that within the stimulated area TMS perceptually facilitates the attributes encoded by the less active neural population. We have demonstrated the generality of this principle for both suprathreshold and subthreshold TMS as well as for colour and orientation-contingent colour using both subjective reports and psychophsyical measures. These findings can explain how TMS disrupts cognitive functions and therefore have implications for all studies which use TMS to disrupt behaviour.